2001
DOI: 10.1200/jco.2001.19.3.812
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Adjuvant Interferon Alfa-2b Treatment

Abstract: On average, patients rate quality of life with melanoma recurrence much lower than even severe IFN alpha-2b toxicity. These results suggest that recurrence-free survival is highly valued by patients. The utilities measured in our study can be applied directly to quality-of-life determinations in clinical trials of adjuvant IFN alpha-2b to measure the net benefit of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 17 publications
8
74
0
1
Order By: Relevance
“…Kilbridge et al found that at least half of low-risk melanoma patients were willing to tolerate mild-moderate and severe IFN toxicity for 4% and 10% improvements, respectively, in 5-year disease-free survival [9]. Krammer and Heinzerling found that patients with melanoma in different stages of the disease showed a high willingness to endure side effects despite very small survival gains (down to 1 extra week) or even only hope with no survival benefit [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kilbridge et al found that at least half of low-risk melanoma patients were willing to tolerate mild-moderate and severe IFN toxicity for 4% and 10% improvements, respectively, in 5-year disease-free survival [9]. Krammer and Heinzerling found that patients with melanoma in different stages of the disease showed a high willingness to endure side effects despite very small survival gains (down to 1 extra week) or even only hope with no survival benefit [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that melanoma patients are willing to endure toxicities for an improvement in survival [9] [10], yet there is a paucity of evidence focused on the preferences of patients with melanoma or oncologists in the value of particular adjuvant treatments where multiple treatment options exist. Moreover, even if patients are eligible for adjuvant treatment, it is unknown whether or not they prefer to receive treatment at this stage, when there is only a risk of recurrence, or wait until a recurrence occurs.…”
Section: Introductionmentioning
confidence: 99%
“…If included, respondents would be required to imagine that they had melanoma but that it was in complete remission; we felt that this may be too complex an undertaking to include as a part of the standard gamble exercise. However, an estimate for living disease free has been reported by Kilbridge as 0.96 (Kilbridge et al, 2001). In addition, our study did not consider health states with multiple toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Health status utility assessments enable the quantification of preferences for health outcomes and the estimation of qualityadjusted life expectancy. Utility measurement in melanoma to date has primarily focused on toxicities associated with interferon (IFN) therapy (Kilbridge et al, 2001;Dixon et al 2006). No studies have obtained utilities for a broader set of health states that capture both the intended (clinical response) and unintended (toxicity) effects of available treatments for advanced melanoma.…”
mentioning
confidence: 99%
“…Kilbridge et al (2001), for instance, used the standard gamble technique to value a series of health states describing the QOL associated with interferon toxicity, melanoma recurrence and disease-free health. Their study, based on 107 patient interviews, showed that the side effects from interferon treatment reduced QoL, from 0.96 for the disease-free health state to 0.81 from severe side effects.…”
Section: Discussionmentioning
confidence: 99%